A survey on various summarization techniques (International Journal of Engineering and Computer Science, 2014)
Text Summarization condenses a document or multiple documents into a smaller version by preserving its information content and the meaning. It is very difficult for a person to manually summarize large documents of text. TextSummarization methods can be classified into extractive and abstractive summarization. There are lots of techniques developed over the years for summarization. In this paper, some of the techniques are studied and reviewed.